If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + 6x + -5 = 19 Reorder the terms: 9 + -5 + 6x = 19 Combine like terms: 9 + -5 = 4 4 + 6x = 19 Solving 4 + 6x = 19 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 6x = 19 + -4 Combine like terms: 4 + -4 = 0 0 + 6x = 19 + -4 6x = 19 + -4 Combine like terms: 19 + -4 = 15 6x = 15 Divide each side by '6'. x = 2.5 Simplifying x = 2.5
| x^3(x-3)(2x+8)=0 | | 1/x-1-1/x-2=0 | | 6y-2(3y-8)+2= | | 10(x+4)=18(x-4) | | 4+5=12 | | 2(c+4)-12= | | 9ln(x)-5=5 | | -5-4t=-14 | | -3-2g=1 | | 12b^2-14b=0 | | 9-6l=-3 | | f(x)=9x^3-13x^2+20+2x^4-36x | | 1650=2310+10x | | 6.1x-2.1(x+2)=3(x+1.5) | | P^2-4p=56 | | 6.1x-2.1(t+2)=3(t+1.5) | | d(sin2t)/dx | | e^8x+5=5 | | 66456/430 | | 5=7m-9 | | 40(s-4)=24s | | (-3c^-1/-3c^-5)^3 | | 2-(6x+3)=11-9x | | 8(t+30)=10t | | 425(x-15)=350(x+15) | | 8(a+4)=64 | | 10=3c-5 | | 9e-5=60.7 | | 48X+11X+X=48729 | | 9p=16.2 | | 48X+11X+X=217 | | 48X+11X+X=2178 |